PENERAPAN METODE DESIGN FOR MANUFACTURING PADA RANCANG BANGUN CNC MILLING 3 SUMBU - yahya, abdurrahman; malik, irawan; zamheri, ahmad (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The use of 3 Axis CNC Milling machines lately is needed by many business actors in the creative industry. However, entrepreneurs sometimes face problems with the cost of CNC Milling machines which are quite expensive. This research focuses on developing the design of 3 Axis CNC Milling machines which are commonly circulating in the market, namely 3 Axis CNC Milling 2418. Researchers develop designs using the Design For Manufacturing method in order to minimize costs but still with good quality. The CAD-CAE program, Solidworks 2021, was used to design and analyze Von Misses stresses and safety factors. The results of the implementation of the DFM method resulted in a 3 Axis CNC Milling design with a minimum cost of 11.9% and a Factor of Safety value of more than 1.